immediately solve the question
Attachments:
![](https://hi-static.z-dn.net/files/dff/35af8717d5959f153d1dee9c382d6cb5.jpg)
Answers
Answered by
0
given, equation
7x^8 - 3x^4 + 5 = 0
7 ( x^4 )^2 - 3x^4 + 5 = 0 ----- (1)
now put x^4 = k , in eq.(1) ,we get
7k^2 - 3k + 5 = 0
which is a quadratic polynomial ,
hence,the given equation is also quadratic.
【 hope it helps 】
7x^8 - 3x^4 + 5 = 0
7 ( x^4 )^2 - 3x^4 + 5 = 0 ----- (1)
now put x^4 = k , in eq.(1) ,we get
7k^2 - 3k + 5 = 0
which is a quadratic polynomial ,
hence,the given equation is also quadratic.
【 hope it helps 】
Similar questions
Hindi,
8 months ago
English,
1 year ago
English,
1 year ago
Accountancy,
1 year ago
Science,
1 year ago